Strengthening Construction, Asset Management, and Revitalization of Social Infrastructure at TPST 3R Gadingkulon - Indra Lukmana Putra; Annisa Fatimah; Moch. Khamim; Novi Nugrahani; Nindia Rizky Ismawa; Andi Kusuma Indrawan; Nugraha Wijayanto (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Community-based waste management systems in developing economies often suffer from fragmented asset governance, reactive maintenance, and underutilized social infrastructure, limiting operational efficiency and sustainability. This study addresses these inefficiencies through a community service intervention at TPST 3R Gading Kulon, Malang City, integrating construction asset management with social infrastructure revitalization. The program adopts a socio-technical systems perspective, repositioning infrastructure as both a functional asset and a platform for community empowerment. The intervention included infrastructure reconfiguration, systematic asset inventory, standardized maintenance protocols, and accountable financial-asset recording systems. Results show significant improvements in infrastructure functionality, asset traceability, and governance quality, while reactivated educational spaces, meeting areas, and waste bank facilities strengthened community participation. The study proposes a scalable, integrative model linking technical asset governance with socio-economic outcomes, supporting SDG 9, SDG 11, and Indonesia's RPJMN 2025–2029.